2001
DOI: 10.1093/ps/80.7.983
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Method for Determination of Carbon Dioxide Content in Egg Yolk and Egg Albumen

Abstract: The safety, quality, and shelf life of shell eggs is a function of carbon dioxide content. A commercial process was recently developed for rapidly cooling shell eggs by using cryogenic CO2. The benefit of this new process over existing cooling processes is that the CO2 addition during cryogenic cooling provides additional safety and quality enhancements. In order for these benefits to be fully developed into a process that can be adopted by the egg industry, and thus realized by the consumer, the amount of CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 4 publications
0
31
0
1
Order By: Relevance
“…As previously reported, the safety, quality and shelf-life of shell eggs are a function of CO 2 content (Keener, LaCrosse, & Babson, 2001). Actually, the beneficial effects of storage in atmospheres enriched in CO 2 on the quality maintenance of fresh eggs are known for many years (Cotterill & Gardner, 1956;Moran, 1937;Sharp, 1930).…”
Section: Introductionmentioning
confidence: 95%
“…As previously reported, the safety, quality and shelf-life of shell eggs are a function of CO 2 content (Keener, LaCrosse, & Babson, 2001). Actually, the beneficial effects of storage in atmospheres enriched in CO 2 on the quality maintenance of fresh eggs are known for many years (Cotterill & Gardner, 1956;Moran, 1937;Sharp, 1930).…”
Section: Introductionmentioning
confidence: 95%
“…In terms of pH ( Figure 2B), the albumen of control samples showed an increasing trend from the beginning to the end of storage caused by CO 2 loss through the shell (Keener et al, 2001;Li et al, 1985). The albumen of samples packed in air evidenced quite constant values of pH during storage, while the use of 100% CO 2 was responsible of a fast and marked pH decrease (of about 1.5-2 points) as a consequence of CO 2 solubilisation in the albumen.…”
Section: Discussionmentioning
confidence: 96%
“…At 0, 24, 48 and 72 h the samples of thin albumen, thick albumen and yolk were analysed to measure the total carbon dioxide content (free and combined) by the chemical method propose by Keener, LaCrosse, and Babson (2001). Brooks and Pace (1938) suggested that the proportion between free and combined CO 2 depends on constituent typology: for the thin albumen the percentage of free CO 2 is about 39%, for the thick albumen is about 40% and for the yolk is about 70%.…”
Section: Section Imentioning
confidence: 99%
“…The yolk samples were posed in 25 ml beaker, reaching a thickness of about 10 mm, similar to yolk radius in eggs. The concentration was measured following the method of Keener, LaCrosse, and Babson (2001) on samples packed in 100% CO 2 atmosphere at 0, 24, 48 and 72 h.…”
Section: Section IVmentioning
confidence: 99%
See 1 more Smart Citation